Integrasi Pendidikan Karakter Berbasis Budaya dalam Perspektif Teori Sosial Kritis: Sebuah Kajian Konseptual - Nismawati Nismawati; Aswanto Aswanto; Muslim Muslim (CV Cendekia Paramartha, 2026)
This conceptual study examines the integration of culture-based character education within the framework of critical social theory by synthesizing interdisciplinary literature on education, culture, and social structures. The analysis reveals that character education is not merely a normative moral transmission process but a socially constructed practice shaped by power relations, ideological interests, and cultural negotiations within educational institutions. Findings indicate that the interaction between cultural values, pedagogical practices, and structural conditions produces a dialectical process in which values are both internalized and contested. Critical social theory provides an analytical lens to uncover how educational systems may reproduce dominant ideologies while simultaneously offering possibilities for emancipation through critical consciousness. The study further identifies that local wisdom, religious values, and global educational demands interact in complex ways that require reflective and contextual interpretation. The proposed integrative framework positions character education as a transformative space that bridges normative, contextual, and critical dimensions. Ultimately, it contributes to reconceptualizing education as a site of social reflection and structural transformation.